The Role of Traditional Micro Institutions, in Income Inequality in Iran - Yadollah Dadgar; Rohollah Nazari (Universitas Trisakti, 2011)
Purpose : Some traditional Iranian micro institutions and also some Shariah micro institutions are working informally along with formal institutions in Iran. This paper is developed to investigate the performance of institutions in question. Although. their shares in whole economy are small, these Iranian-Islamic Micro Institutions. IMI. do play their own role on changing the related economic variables, including inequality and income distribution in Iran. A specific purpose of this paper is testing the above relationships. Design/methodology/approach: In this paper firstly, and by using library studies, we explain 3 constituents of IMI. Secondly, and in order to project the impacts of variables in question on the income distribution in Iran, we gather the required data. Sources of our data include central bank of Iran, CBI, Awqaf organization and charity affairs of Iran, AOL and Statistic Centre of Iran. Thirdly, and for statistical analyzing, and statistical inferences, we employ econometric models. Finally we use vector autoregressive method (VAR), to investigate the relationship between variables, based on time series data (for 1974-2009 periods). Findings: The results of this paper show that: 1- the performance of Iranian-Islamic Micro institutions, MI including two Shariah payment subsystems and a traditional Waqf institution, reduce the inequality and improve the distributions of income.2-comparing the impact of IMI with Iranian government size ,the government size worsens the inequality of income. In other word, the bigger the government size the, worse the income inequality, but the more Waqf revenue and Shariah payments, the better income distribution.3-In Iran, these three informal institutions, surprisingly, in some dimensions, compete with formal institutions. Mean while, the deeper the belief of the people, the more efficient the